2011
DOI: 10.3324/haematol.2011.042937
|View full text |Cite
|
Sign up to set email alerts
|

Minimal residual disease in peripheral blood at day 15 identifies a subgroup of childhood B-cell precursor acute lymphoblastic leukemia with superior prognosis

Abstract: The online version of this article has a Supplementary Appendix. BackgroundMost minimal residual disease-directed treatment interventions in current treatment protocols for acute lymphoblastic leukemia are based on bone marrow testing, which is a consequence of previous studies showing the superiority of bone marrow over peripheral blood as an investigational material. Those studies typically did not explore the prognostic impact of peripheral blood involvement and lacked samples from very early time points of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
20
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 37 publications
2
20
0
Order By: Relevance
“…Another interesting point is the high applicability of MFC-MRD observed in our study where all samples were informative, as reported in BM (17) but also in rare PB studies (20,21). At variance with RT-PCR which is only informative for 80-95% of the patients (18), MFC also does not require diagnosis material to be preserved, since diagnosis data remain available at all times in silico for comparison with MRD samples.…”
Section: Discussionsupporting
confidence: 58%
“…Another interesting point is the high applicability of MFC-MRD observed in our study where all samples were informative, as reported in BM (17) but also in rare PB studies (20,21). At variance with RT-PCR which is only informative for 80-95% of the patients (18), MFC also does not require diagnosis material to be preserved, since diagnosis data remain available at all times in silico for comparison with MRD samples.…”
Section: Discussionsupporting
confidence: 58%
“…With our growing understanding of the prognostic significance of early responses and the clearance of minimal residual disease in other hematologic malignancies, we found that, among those with IDH1/2 mutations receiving induction chemotherapy, a decrease in serum 2HG levels on day 14 with respect to the baseline was associated with significantly improved EFS and OS, even when we accounted for transplantation. This time point is relevant because many patients will have an ablated marrow, and other markers of residual disease may be less sensitive in that state.…”
Section: Discussionmentioning
confidence: 96%
“…Our results on patients treated with BFM‐type therapy are partially in line with these data, although in terms of chemotherapy intensity, the COG protocol day 8 better compares with day 15 in BFM. A first hint toward the usefulness of PB‐MRD for BFM‐type protocols came from Czech authors, who considered that PCR is not the right method for rapid result turnaround contrary to what is feasible using FCM. Our results now broaden the view on this matter.…”
Section: Discussionmentioning
confidence: 99%
“…Some authors therefore reasoned that PB is not appropriate for MRD‐based outcome prognostication in B‐ALL. However, quantifying MRD in PB of children with B‐ALL does correlate with outcome and might even allow separating different risk groups, if respective time points and/or thresholds of MRD in PB differ from those used in BM …”
Section: Introductionmentioning
confidence: 99%